High-resolution and large-size stretchable electrodes based on patterned silver nanowires composites - Lin, Yong; Li, Qingsong; Ding, Chen; Wang, Jiayi; Yuan, Wei; Liu, Zhiyuan; Su, Wenming; Cui, Zheng (Nano research, 2022)
Electrodes based on composites of silver nanowires (AgNWs) and elastic polymers have been widely studied and applied in various stretchable electronic devices. However, due to the high aspect ratio of nanowires, the patterning of AgNW-based composite electrodes remains a huge challenge, especially for high-resolution complex circuit wiring on large-size elastic substrates. In this paper, we propose a method for preparing large-size stretchable circuit boards with high-resolution electrodes by the combination of screen printing and vacuum filtration of AgNWs/polydimethylsiloxane (PDMS) composite. The as-prepared stretchable electrodes have smooth edges with patterning resolution up to ∼50 µm. The conductivity of the composite electrode can be precisely controlled by varying deposition densities of AgNWs and have reached to 1.07 × 10 4 S/cm when the deposition density was 2.0 mg/cm 2 . In addition, the uniformity of conductivity and the resistance-strain characteristics of composite electrodes were systematically evaluated with different AgNWs deposition densities. The composite electrodes have been successfully employed to construct a large-size programmable display system and an 18-channel surface electromyography (EMG) recording, showing great potentials for some strain-insensitive stretchable circuits in wearable and health-related electronic applications.